2013
DOI: 10.1007/s10059-013-0221-8
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus (HCMV) US2 Protein Interacts with Human CD1d (hCD1d) and Down-Regulates Invariant NKT (iNKT) Cell Activity

Abstract: To avoid host immune surveillance, human cytomegalovirus (HCMV) encoded endoplasmic reticulum (ER)-membrane glycoprotein US2, which interferes with antigen presenting mechanism of major histocompatibility complex (MHC) class Ia and class II molecules. However, not many attempts have been made to study the effect of HCMV US2 on the expression of MHC class Ib molecules. In this study, we examined the effect of HCMV US2 on the expression and function of human CD1d (hCD1d), which presents glycolipid antigens to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…As a result of coevolution, most, if not all, herpesviruses have developed intricate mechanisms by which to modulate host immune systems for the benefit of viral survival (6). Because of the importance of NKT cells in antiviral immunity, viruses in all three major herpesvirus families (alpha-, beta-, and gammaherpesviruses) have evolved viral mechanisms to evade CD1d and NKT cell function (7)(8)(9)(10)(11)(12). We and others have shown that herpes simplex virus 1 (HSV-1), the prototype alphaherpesvirus, has evolved to downregulate CD1d expression in antigen-presenting cells and evade NKT cell function (10,13,14).…”
mentioning
confidence: 99%
“…As a result of coevolution, most, if not all, herpesviruses have developed intricate mechanisms by which to modulate host immune systems for the benefit of viral survival (6). Because of the importance of NKT cells in antiviral immunity, viruses in all three major herpesvirus families (alpha-, beta-, and gammaherpesviruses) have evolved viral mechanisms to evade CD1d and NKT cell function (7)(8)(9)(10)(11)(12). We and others have shown that herpes simplex virus 1 (HSV-1), the prototype alphaherpesvirus, has evolved to downregulate CD1d expression in antigen-presenting cells and evade NKT cell function (10,13,14).…”
mentioning
confidence: 99%
“…An interesting finding was the observation in PHIP of downregulation of CD1D (data not shown), a nonclassical HLA class I molecule that recognizes NKT cell TCR. HCMV has been shown to downregulate CD1d at the transcriptional level, thereby acting as an immune escape mechanism (45). This extensive study shows that during the symptomatic stage of acute HCMV infection, PHIP mounted appropriate cellular immune responses.…”
Section: Discussionmentioning
confidence: 83%
“…US2 and US11 induce rapid translocation of MHC class I heavy chains from the ER into the cytosol and subsequent degradation by the proteasome ( 271 , 272 ). US2 and US11 also physically interact with CD1d but do not downregulate CD1d surface expression ( 273 , 274 ). However, reduced activation of iNKT cells after stimulation with αGalCer-pulsed US2-expressing APCs has been reported but the underlying mechanism is unclear ( 274 ).…”
Section: Viral Evasion Of Cd1-restricted T Cellsmentioning
confidence: 99%